1983
DOI: 10.1073/pnas.80.14.4450
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a precursor molecular for the RNA moiety of the processing enzyme RNase P.

Abstract: A precursor molecule for lOSb (MI) RNA, the RNA moiety of the RNA processing enzyme ribonuclease P (EC 3.1.26.5), is accumulated transiently in an Escherichia coli strain containing a plasmid that carries the lOSb RNA gene. The same RNA precursor molecule is accumulated, in relatively large quantities, in a temperature-sensitive RNase E-mutant at the nonpermissive temperature. The RNA precursor includes lOSb RNA and an extra 3' fragment that contains a termination stem and loop. It can be processed in vitro to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…DNA sequencing of the PCR product of the rnpB gene encoding M1 RNA indicated that the sequence of the gene downstream of the mature 3Ј terminus in the mutant is GATTT, the same as that published previously (14,15), and the same as the wild-type precursor sequence (Table 2). Thus, we conclude that the A residues in the third and fourth positions must be added posttranscriptionally.…”
Section: Methodsmentioning
confidence: 51%
See 1 more Smart Citation
“…DNA sequencing of the PCR product of the rnpB gene encoding M1 RNA indicated that the sequence of the gene downstream of the mature 3Ј terminus in the mutant is GATTT, the same as that published previously (14,15), and the same as the wild-type precursor sequence (Table 2). Thus, we conclude that the A residues in the third and fourth positions must be added posttranscriptionally.…”
Section: Methodsmentioning
confidence: 51%
“…However, products were found to accumulate in some exoribonuclease-deficient strains that contained as many as 10 extra nucleotides at their 3Ј ends (8). Likewise, in a recent study of the maturation of M1 RNA, the catalytic subunit of RNase P, products with up to six additional 3Ј residues were observed (9), despite the fact that RNase E is thought to cleave this precursor at a position only one or two nucleotides downstream from the mature 3Ј terminus (14,15).…”
mentioning
confidence: 99%
“…However, some of the rne-dependent sites listed in Table 1 must be considered to be only putative sites because cleavage by RNase E in vitro has not been demonstrated. A few rae-dependent sites are apparently not cleaved by partially purified RNase E Gurevitz et al 1983;Nilsson et al 1988;Subbarao and Apirion 1989) but by other activities like RNase K (Lunberg et al 1990), RNase F (Gurevitz et al 1982), or RNase 111 (Srivastava et al 1990). …”
mentioning
confidence: 99%
“…5). Multiple transcripts arising from any of three promoters can be processed at the 3' end to remove a 38-nucleotide terminator sequence (13,14,28 (13). An RNA processing event which removes the terminator stem and loop could remove this messenger sequence from the nascent Mi RNA in unterminated RNA.…”
Section: Resultsmentioning
confidence: 99%